Development of Digital Forensic Framework for Anti-Forensic and Profiling Using Open Source Intelligence in Cyber Crime Investigation - Hakim, Muhamad Faishol; Alamsyah, Alamsyah (Recursive Journal of Informatics, 2024)
Abstract. Cybercrime is a crime that increases every year. The development of cyber crime occurs by utilizing mobile devices such as smartphones. So it is necessary to have a scientific discipline that studies and handles cybercrime activities. Digital forensics is one of the disciplines that can be utilized in dealing with cyber crimes. One branch of digital forensic science is mobile forensics which studies forensic processes on mobile devices. However, in its development, cybercriminals also apply various techniques used to thwart the forensic investigation process. The technique used is called anti-forensics. Purpose: It is necessary to have a process or framework that can be used as a reference in handling cybercrime cases in the forensic process. This research will modify the digital forensic investigation process. The stages of digital forensic investigations carried out consist of preparation, preservation, acquisition, examination, analysis, reporting, and presentation stages. The addition of the use of Open Source Intelligence (OSINT) and toolset centralization at the analysis stage is carried out to handle anti-forensics and add information from digital evidence that has been obtained in the previous stage. Methods/Study design/approach: This research will modify the digital forensic investigation process. The stages of digital forensic investigations carried out consist of preparation, preservation, acquisition, examination, analysis, reporting, and presentation stages. The addition of the use of Open Source Intelligence (OSINT) and toolset centralization at the analysis stage is carried out to handle anti-forensics and add information from digital evidence that has been obtained in the previous stage. By testing the scenario data, the results are obtained in the form of processing additional information from the files obtained and information related to user names. Result/Findings: The result is a digital forensic phase which concern on anti-forensic identification on media files and utilizing OSINT to perform crime suspect profiling based on the evidence collected in digital forensic investigation phase. Novelty/Originality/Value: Found 3 new types of findings in the form of string data, one of which is a link, and 7 new types in the form of usernames which were not found in the use of digital forensic tools. From a total of 408 initial data and new findings with a total of 10 findings, the percentage of findings increased by 2.45%.